Calidad de atención y satisfacción de los usuarios que acuden a la droguería Gloria Iquitos 2024 - Pupuche Isuiza, Juana Dora (2025)
Within the study, a quantitative-descriptive and correlational approach was used, employing a non-experimental design to evaluate the variables in question. The research sought to measure and analyze the variables. The relevant findings indicated an increased correlativity, with Spearman's Rho equal to 0.977 and a bilateral significance of 0.000, lower than the threshold of 0.05, which supports the hypothesis proposed. This suggests that there is evidence of a significant link between the variables examined. In conclusion, it was established that improvements in the quality of care are associated with an increase in user satisfaction. This finding is relevant, as it highlights the importance of the first variable in the field of health and customer service, indicating that strategies aimed at optimizing care can have a positive impact on user satisfaction, which is fundamental for customer loyalty and long-term success of the pharmacy.